Teacher efficacy and its impact on students’ learning / Norazean Sulaiman - Sulaiman, Norazean (2015)
Teacher efficacy is believed to give influence on students’ learning. According to Tschannen and Woolfolk (2010), teachers are responsible to bring about positive outcomes for the students by helping them in their learning process. A considerable amount of research has been done to investigate the influence of teacher efficacy on students’ learning, but less attention has been paid on the influence of teacher efficacy towards ESL learners in tertiary level, especially in the Malaysian context. Thus, the present study was aimed at investigating the impact of teacher efficacy on students’ learning by focusing on the students’ perception towards learning English, students’ achievement in English, students’ motivation in learning English, and students’ participation in learning English. Five lecturers teaching English at the foundation level and 15 students from the five classes were selected to participate in the study. Observation and interview were chosen as means of data collection. The findings indicated that the students have positive perception towards learning English from high self-efficacy lecturers. The findings also showed that the students’ achievements were improving in all four English skills. Additional to that, the research also managed to identify how the teachers with high self-efficacy influence students’ motivation in learning English. Last but not least, the findings showed that the highly efficacious lecturers did influence their students’ participation in learning English. In conclusion, this study provided evidences that teacher efficacy brings positive impact on students’ learning. Therefore, the high self-efficacy characteristics need to be nurtured in the teachers for the establishment of an effective learning among the students.